1898 Ala. Laws 190 - (:unkn) unknown (My University, 1898)
Placed a one hundred dollar tax on dealers of pistols, Bowie knives, or dirk knives of one hundred dollars. Also taxed dealers of pistol and rifle cartridges at ten dollars.
Keywords: TAX - DEALERS